2002
DOI: 10.1142/s0218271802002062
|View full text |Cite
|
Sign up to set email alerts
|

Thomas–fermi–dirac Model for Low Density Stellar Matter in the Presence of a Strong Quantizing Magnetic Field

Abstract: The effect of strong quantizing magnetic field on low density stellar matter is investigated using Thomas-Fermi-Dirac (TFD) model. The Wigner-Seitz cell structure is assumed for the low density matter. The significant changes in the properties of such low density matter in presence of strong magnetic fields are discussed. It is seen that the decay time scale for magnetic field decreases by at least two orders of magnitude in such a model calculation.PACS numbers: 12.38. Mh, 12.15.Ji, 95.30.Cq, 97.60.Jd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In one of the previous calculations we also made a preliminary study of low density crustal matter of neutron stars in presence of strong quantizing magnetic field using the Thomas-Fermi-Dirac approach. The model was non-relativistic in nature and occupancy of only the zeroth Landau level was taken into account [38]. In some work, more than a decade ago, Shivamogi and Mulser did some relativistic calculation for atoms in ultra-strong magnetic field [39].…”
Section: Relativistic Thomas-fermi-dirac Model In Quantizing Magneticmentioning
confidence: 99%
“…In one of the previous calculations we also made a preliminary study of low density crustal matter of neutron stars in presence of strong quantizing magnetic field using the Thomas-Fermi-Dirac approach. The model was non-relativistic in nature and occupancy of only the zeroth Landau level was taken into account [38]. In some work, more than a decade ago, Shivamogi and Mulser did some relativistic calculation for atoms in ultra-strong magnetic field [39].…”
Section: Relativistic Thomas-fermi-dirac Model In Quantizing Magneticmentioning
confidence: 99%
“…Generalized versions of non-relativistic as well as relativistic form of Thomas-Fermi equations in presence of strong quantizing magnetic field, when the Landau levels for the electrons are populated have also been obtained [7,9,10]. The thermodynamic properties of matter inside the magnetically deformed WS cells have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, to the best of our knowledge, no studies have been reported on the two dimensional Thomas-Fermi model for electron gas in presence of strong quantizing orthogonal magnetic field, in which the Landau levels are populated for the electrons. Again, in the three dimensional case, incorporating electron-electron exchange interaction, a modified form of Thomas-Fermi equation, called the Thomas-Fermi-Dirac equation has been developed both for non-relativistic as well as for relativistic electron gas with or without the presence of magnetic field [5,6,7,8,9]. Unfortunately, no such formalism has been developed in the case of two dimension.…”
Section: Introductionmentioning
confidence: 99%